2016
DOI: 10.1186/s12883-016-0644-x
|View full text |Cite
|
Sign up to set email alerts
|

Association between vertebral artery hypoplasia and posterior circulation stroke

Abstract: BackgroundThe clinical significance of vertebral artery (VA) hypoplasia is under discussion. The aim of this retrospective study is to evaluate a hypothesis of a possible causal link between VA hypoplasia (VAH) and the incidence of posterior circulation stroke (PCS) or TIA depending on the degree of VAH  and vascular risk factors.MethodsA total of 367 symptomatic (PCS or TIA) and 742 asymptomatic subjects, were selected to participate in the study. The extracranial arteries were examined by ultrasound. VAH was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
50
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 13 publications
(43 reference statements)
3
50
0
3
Order By: Relevance
“…A significantly higher frequency of vertebral artery hypoplasia in the posterior circulation infarction group (44.75%; Table ) and a high correlation with vertebral artery territory ischemic stroke (55.56%) were noted. These results were consistent with previous clinical studies and further highlight the importance of vertebral artery hypoplasia in posterior circulation infarction …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A significantly higher frequency of vertebral artery hypoplasia in the posterior circulation infarction group (44.75%; Table ) and a high correlation with vertebral artery territory ischemic stroke (55.56%) were noted. These results were consistent with previous clinical studies and further highlight the importance of vertebral artery hypoplasia in posterior circulation infarction …”
Section: Discussionsupporting
confidence: 93%
“…Traditionally, basilar artery or distal vertebral artery stenosis is considered an important risk factor for brain stem stroke. 1,3,[6][7][8] In recent years, series of studies pointed out a possible correlation between vertebral artery hypoplasia [9][10][11][12][13] and posterior circulation infarction. Cohort studies also supported clinical observations that a hypoplastic vertebral artery aggravates the vascular risk for posterior circulation infarction synergistically.…”
mentioning
confidence: 99%
“…From the viewpoint of hemodynamics, statistically significant differences in the side‐to‐side extracranial vertebral flow volume indicate the possibility of chronic hypoperfusion over the vertebrobasilar system. Several studies reported the importance of VAH‐related inadequate net VA flow or low velocity, eventually in a higher incidence of stroke events, particularly in the ipsilateral posterior circulations . A compensatory mechanism by which the contralateral VA becomes dominant to achieve the adequate blood flow for brain circulation has also been reported .…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, both conditions contribute to the extent of ischemic strokes and especially posterior circulation strokes in the vertebrobasilar arterial territory . In addition, among patients with unilateral VAH, a trend of both arterial dilatation over the other dominant VA and elongation to the BA has been observed .…”
mentioning
confidence: 99%
“…Radio-ligands are preferred because they can transform normally nonspecific radioisotopes into targeted agents to specifically bind to certain types of tissue which causes the radioisotope to accumulate in desired areas of the body, thereby increasing the amount of signal seen in the image in that area. FDA-approved radioisotopes include the following: 11 C, 14 C, 13 N, 15 O, 18 F, 67 Ga, 82 Rb, 89 Zr, 89 Sr, 90 Y, 99 Mo, 99 Tc, 111 In, 123 I, 125 I, 131 I, 133 Xe, 153 Sm, 201 Tl, and 223 Ra. Both labelled radiotracers and radioisotopes are injected into a patient and the natural decay process of the isotopes occurs inside the body while detectors monitor the radiation given off from the decay process in order to create images.…”
Section: Tomography (Spect) (1961)mentioning
confidence: 99%